Hakekat Kepribadian dalam Psikologi Islam - Muhammad Ali (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
This article discusses about the man as God’s creation that is perfect when compared with his inventions to the other. Man given by the God of reason and passions as well as qalbu. However, if a human is dominating his, then he will be human evil. Meanwhile, in which dominate it is reasonable then he will be somebody who is unstable. In the human it is the dominating qalbu, all other components will be easily controlled so created is a kindness or tranquility.